Analisis Dampak Media Sosial Terhadap Penjualan Perumahan: Studi Empiris Penggunaan Iklan Facebook dan Instagram - Rully Armanto; Muji Gunarto (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
The development of digital technology is growing rapidly, as well as digital-based marketing activities. Because advertising marketing is the most important part of marketing, of course there are also many kinds of advertising media. In this study, researchers examined Facebook and Instagram social media ads, this study aims to determine how widespread or influence Facebook and Instagram social media ads have on home sales in Palembang. The population in this study is the people of Palembang City who live in Palembang City Housing. The results of this study indicate that both Facebook and Instagram social media ads have a positive effect on sales, but when compared with Facebook social media ads. Instagram has a significant influence.